2005
DOI: 10.1161/01.cir.0000160864.31351.c1
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Unfolded Protein Response Occurs at All Stages of Atherosclerotic Lesion Development in Apolipoprotein E–Deficient Mice

Abstract: Background-Apoptotic cell death contributes to atherosclerotic lesion instability, rupture, and thrombogenicity. Recent findings suggest that free cholesterol (FC) accumulation in macrophages induces endoplasmic reticulum (ER) stress/unfolded protein response (UPR) and apoptotic cell death; however, it is not known at what stage of lesion development the UPR is induced in macrophages or whether a correlation exists between UPR activation, FC accumulation, and apoptotic cell death. Methods and Results-Aortic ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

19
265
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 269 publications
(286 citation statements)
references
References 58 publications
19
265
0
Order By: Relevance
“…The model described here is specifically relevant to processes involved in advanced lesion morphology, and so the roles of SRA and TLR4 on advanced lesional macrophage death and plaque necrosis represent an important area for future study. Advanced plaques also contain molecules or conditions that promote calcium-based ER stress, including atherogenic lipoproteins and peroxynitrite (8,13), and lesional macrophages display multiple markers of UPR activation in vivo (9,10). Moreover, we recently found that the apoptosis pathway described here is enhanced in insulin-resistant macrophages both in vitro and in advanced atherosclerotic lesions, and the advanced lesions of humans with type II diabetes are characterized by increased lesional macrophage death and plaque necrosis (48,49).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The model described here is specifically relevant to processes involved in advanced lesion morphology, and so the roles of SRA and TLR4 on advanced lesional macrophage death and plaque necrosis represent an important area for future study. Advanced plaques also contain molecules or conditions that promote calcium-based ER stress, including atherogenic lipoproteins and peroxynitrite (8,13), and lesional macrophages display multiple markers of UPR activation in vivo (9,10). Moreover, we recently found that the apoptosis pathway described here is enhanced in insulin-resistant macrophages both in vitro and in advanced atherosclerotic lesions, and the advanced lesions of humans with type II diabetes are characterized by increased lesional macrophage death and plaque necrosis (48,49).…”
Section: Discussionmentioning
confidence: 72%
“…In this model, macrophage apoptosis is triggered by the endoplasmic reticulum (ER) stress pathway known as the unfolded protein response (UPR) in combination with engagement of the macrophage type A scavenger receptor (SRA), but not by either stimulus alone (8). The UPR is activated in advanced murine and human atherosclerotic lesions (9)(10)(11), and these lesions are known to contain a number of UPR activators (e.g., oxidant stress and nitric oxide) and SRA ligands (e.g., oxidized lipoproteins and advanced glycosylation end products) (12)(13)(14). Moreover, subpopulations of macrophages in apoptotic-rich areas of lesions are filled with lipoprotein-derived free cholesterol (FC) (15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…Interestingly, HMEC-1 cells silenced for CHOP by siRNA, or fibroblasts issued from CHOP-/-mice, 32 were partly resistant to the cytotoxic effect of oxLDLs, which supports a role for ER stress and CHOP in oxLDLs-mediated apoptosis, in agreement with Tabas et al 34 Moreover, we show that HDLs inhibit the phosphorylation of JNK induced by oxLDLs, which in our system is activated by IRE1a, and is involved in ER stress-dependent apoptosis 9, via the JNK proapoptotic pathway, as reported. 40 The effect of oxLDLs and HDLs on ER stress-induced apoptosis is also favoured by caspase-12 processing that occurs upon oxLDLs stimulation and which is inhibited by HDLs in murine 25 However, the precise role of caspase-12 in human is still undefined and need further investigation as human caspase-12 gene encodes an aberrant caspase. Altogether, these data emphasize the inhibitory effect of HDLs on ER stress as a major feature in HDLs antiapoptotic mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Our in vitro data suggest that HDLs by blocking the Ca 2 þ deregulation, and consequently both ER stress and autophagy, may reduce the level of ER stress and autophagy markers that are detected in early and advanced atherosclerotic lesions. 9,15,34,40 Evaluation of cytotoxicity, necrosis and apoptosis. For cytotoxicity experiments, cells were serum starved for 24 h and stimulated for the indicated times at 371C.…”
Section: Discussionmentioning
confidence: 99%
“…First, a profound increase in IRE1 phosphorylation and XBP1s expression is observed in atherosclerotic plaques of mice and humans (8,10). Second, mechanical sheer stresses activate IRE1, whereas cardiovascular disease risk factors, such as oxidized phospholipids and homocysteine, induce both IRE1 and PERK (5,(25)(26)(27)(28)(29). Third, experimentally sustained Xbp1 mRNA splicing in the vessel wall promotes atherosclerosis, whereas its ablation ameliorates hypercholesterolemia in obese or apolipoprotein E-deficient (ApoE −/− ) mice (10,30).…”
mentioning
confidence: 99%